Teach yourself Korean - Vincent, Mark 1974-; Yeon, Jaehoon (Chicago, Ill. McGraw-Hill, 2003)
Introduces spoken and written Korean for beginners or as a refresher course for those who have studied the language.
In English and Korean.
Keywords: Korean language -- Study and teaching -- English speakers; Korean language -- Self-instruction.